1988
DOI: 10.1002/jts.2490010302
|View full text |Cite
|
Sign up to set email alerts
|

The trauma spectrum: The interaction of biological and social events in the genesis of the trauma response

Abstract: When Kardinerfirst described the full syndrome of what is now called PTSD in 1941, he called the trauma response a 'physioneurosis," that is, a mental disorder which affects both the soma and the psyche. Now, more than 40 years later much knowledge has been gained about the biological effects of traumatization. Based on the studies of disruptions of attachment bonds innon-human primates, the animal model of inescapable shock, and numerous studies of traumatized children and adults, we are beginning to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(59 citation statements)
references
References 70 publications
0
57
1
1
Order By: Relevance
“…The role of the HPA axis in memory im pairment is supported by several animal and human studies [146,160,161]. In animal experiments, it has been shown that CRH administration has an inverted U dose-re sponse effect on learning and performance [146].…”
Section: Receptor-binding a Ffinitymentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the HPA axis in memory im pairment is supported by several animal and human studies [146,160,161]. In animal experiments, it has been shown that CRH administration has an inverted U dose-re sponse effect on learning and performance [146].…”
Section: Receptor-binding a Ffinitymentioning
confidence: 99%
“…In animal experiments, it has been shown that CRH administration has an inverted U dose-re sponse effect on learning and performance [146]. In addition, in humans it has been shown that the hippocampus is rich in corti costerone receptors which are selectively acti 214 Vgontzas/Kalcs/Bixlcr M echanism s o f Benzodiazepine Side Effects vated during stress [160,161]. In turn, an increase in corticosteroid levels can suppress hippocampal function and thus cause amne sia.…”
Section: Receptor-binding a Ffinitymentioning
confidence: 99%
“…Yet, patients suffering BPD cannot perceive the immediate connection between their symptoms and early abusive experiences (28). On a related note, previous follow-up studies (29) demonstrate that fragments of trauma may be transformed through the time and revealed in different forms, such as somatoform, behavioral reenactment, or dissociated personality. In this regard, BPD is considered to be the representing form of adaptation to chronic abuse and traumatic events.…”
Section: Discussionmentioning
confidence: 99%
“…Another lesson of the sarin gas attacks on the Tokyo subway system, also supported by other empirical findings and theoretical perspectives, is that trauma victims may manifest their symptoms cognitively, socially, behaviorally, emotionally, as well as physically (Van der Kolk, 1988;Van der Kolk, 1994;Krystal, et al, 1989). The assessment of posttrauma symptomatology reported by Kawana, et al (2005) purposely included physical symptoms in an effort to detect and measure "masked PTSD" in sarin gas attack survivors.…”
Section: Behavioral Health Preparedness and Treatment For Disaster VImentioning
confidence: 94%